Consensus on surgical aspects of managing osteomyelitis in the diabetic foot. Issue 1 (1st January 2016) - Allahabadi, Sachin; Haroun, Kareem B.; Musher, Daniel M.; Lipsky, Benjamin A.; Barshes, Neal R.
Abstract : Background: The aim of this study was to develop consensus statements that may help share or even establish 'best practices' in the surgical aspects of managing diabetic foot osteomyelitis (DFO) that can be applied in appropriate clinical situations pending the publication of more high-quality data. Methods: We asked 14 panelists with expertise in DFO management to participate. Delphi methodology was used to develop consensus statements. First, a questionnaire elicited practices and beliefs concerning various aspects of the surgical management of DFO. Thereafter, we constructed 63 statements for analysis and, using a nine-point Likert scale, asked the panelists to indicate the extent to which they agreed or disagreed with the statements. We defined consensus as a mean score of greater than 7.0. Results: The panelists reached consensus on 38 items after three rounds. Among these, seven provide guidance on initial diagnosis of DFO and selection of patients for surgical management. Another 15 statements provide guidance on specific aspects of operative management, including the timing of operations and the type of specimens to be obtained. Ten statements provide guidance on postoperative management, including wound closure and offloading, and six statements summarize the panelists' agreement on general principles for surgical management of DFO. Conclusions: Consensus statement on the perioperative management of DFO were formed with an expert panel comprised of a variety of surgical specialties. We believe these statements may serve as 'best practice' guidelines until properly performed studies provide more robust evidence to support or refute specific surgical management steps in DFO.